Penggunaan Powerpoint sebagai Media Pembelajaran Daring untuk Mengembangkan Motivasi Belajar di TK Plus Roudhoh - Nida Nur Fadillah; Fivi Triyulia; Aida Ash Sholehah; Nahrowi Adjie (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
Learning media is one of the main things that must be present in learning activities. The learning media will help clarify educators' intention to a certain material to their students, no exception for the preschool level. Given the current condition of the Covid-19 pandemic, the media user needs to adjust to the situation but still adapt to the needs of early childhood. As for online learning that has been long enough, it is not uncommon to make children feel saturation during virtual face-to-face learning; this encourages implementers to solve the problem by using PowerPoint as an online learning medium. Moreover, PowerPoint can provide visuals that can attract the attention of the child. As a result, the use of PowerPoint media makes children more active and enthusiastic in learning. Therefore, PowerPoint can be one of the media that can be used in online learning.